فعّالية استخدام طريقة "المفتاح للعلوم" لترقيّة كفاءة الطلاب في استيعاب علم النحو بالمدرسة التربيّة الإسلاميّة جندونج أغام - ذاكيا, ذاكيا; يسرى, أوكتا رينا (Asian Journal of Islamic Studies and Da'wah, 2023)
Teaching grammar to students is one of the important subjects that need to choose and use the appropriate educational method for the conditions of students and their ability to understand the study. The educational method is the system used by teachers to achieve and communicate information to the minds of students in a way that improves the goals of education. In education, teachers use different methods to communicate the material to students in their classes so that the study goals are achieved. The researcher used experimental quantitative research to find out the effectiveness of using the "Key to Science" method to upgrade students' competence in understanding grammar. The community in this research is students in the first semester of the Islamic Educational School of Gundong and the researcher takes the sample in a proposive sampling way. The research tools used are observation and testing. The researcher used the research analysis as the "T" test base. The average result of the post-test in the experimental semester is 82.41. The average result of the post-test in the control class is 77.27. The researcher found that the result of the calculation (2.448) and the table (2.003) The result of the calculation is greater than the table and therefore the null hypothesis is returned and the alternative hypothesis is acceptable. The effectiveness of using the key to science method to upgrade students' competence in understanding grammar is 76-99% They absorb students in most teaching subjects The average score is 82.41. The researcher takes the conclusion that there is an effective use of the “key to science” method to upgrade the efficiency of students in absorbing grammar in the Islamic educational school of Canduang Agam.